Bioorthogonal “Click and Release” Reaction‐Triggered Aggregation of Gold Nanoparticles Combined with Released Lonidamine for Enhanced Cancer Photothermal Therapy - Yan, Xiao; Li, Ke; Xie, Tian‐Qiu; Jin, Xiao‐Kang; Zhang, Cheng; Li, Qian‐Ru; Feng, Jun; Liu, Chuan‐Jun; Zhang, Xian‐Zheng (Angewandte Chemie International Edition, 2024)
Cancer has been the most deadly disease, and 13 million cancer casualties are estimated to occur each year by 2030. Gold nanoparticles (AuNPs)‐based photothermal therapy (PTT) has attracted great interest due to its high spatiotemporal controllability and noninvasiveness. Due to the trade‐off between particle size and photothermal efficiency of AuNPs, rational design is needed to realize aggregation of AuNPs into larger particles with desirable NIR adsorption in tumor site. Exploiting the bioorthogonal “Click and Release” (BCR) reaction between iminosydnone and cycloalkyne, aggregation of AuNPs can be achieved and attractively accompanied by the release of chemotherapeutic drug purposed to photothermal synergizing. We synthesize iminosydnone‐lonidamine (ImLND) as a prodrug and choose dibenzocyclooctyne (DBCO) as the trigger of BCR reaction. A PEGylated AuNPs‐based two‐component nanoplatform consisting of prodrug‐loaded AuNPs‐ImLND and tumor‐targeting peptide RGD‐conjugated AuNPs‐DBCO‐RGD is designed. In the therapeutic regimen, AuNPs‐DBCO‐RGD are intravenously injected first for tumor‐specific enrichment and retention. Once the arrival of AuNPs‐ImLND injected later at tumor site, highly photothermally active nanoaggregates of AuNPs are formed via the BCR reaction between ImLND and DBCO. The simultaneous release of lonidamine further enhanced the therapeutic performance by sensitizing cancer cells to PTT. We reported the application of bioorthogonal “Click and Release” (BCR) reaction between prodrug iminosydnone‐lonidamine (ImLND) and dibenzocyclooctyne (DBCO) to form highly photothermal‐active nanoaggregates with synergistic drug release. The reactants of BCR reaction were grafted on surface of gold nanoparticles (AuNPs) and was proven both in vitro and in vivo to robustly enhance the therapeutic outcome of photothermal therapy.